Two‐step selenization using nozzle free Se shower for Cu(In, Ga)Se2 thin film solar cell. (12th December 2017) - Song, Yu Jin; Kang, Jeong‐Yoon; Baek, Gun Yeol; Bae, Jin A; Yang, So Hyun; Jeon, Chan‐Wook
Abstract: The production of commercialized Cu(In, Ga)(S, Se)2 (CIGS) photovoltaic absorber layers uses expensive H2 Se gas with a high utility cost. To reduce the manufacturing cost of CIGS photovoltaic modules, a process technology capable of supplying Se vapor uniformly over a large area is required to replace H2 Se. In this study, a nozzle‐free Se shower was implemented using a porous material to pass Se vapor while confining liquid Se, and the highly effective selenization of the CuInGa precursor was performed. The nozzle‐free Se‐shower vehicle could be mounted in a commercial rapid thermal process chamber. The chamber pressure and the temperatures of the shower module and substrate, which were controlled independently by the upper and lower heaters, respectively, were varied to control the amount of Se supplied during the entire selenization reaction in real time. In particular, the precursor should be soaked with a sufficient amount of Se at a relatively low substrate temperature of 300°C or less to obtain a good quality absorber. In addition, at a chamber pressure of 100 Torr during the soaking stage, the Ga content in the surface region of the absorber increased considerably with a concomitant improvement in the open‐circuit voltage. The highest performance obtained using this method was an open‐circuit voltage of 0.638 V, short‐circuit current density of 34 mA/cm 2, fill factor of 67.2%, and an active area efficiency of 14.57%. This performance is very high compared with other CIGS solar cells manufactured by a 2‐step process using Se vapor. Abstract : Realization of a nozzle‐free Se shower using a porous medium that selectively passes Se vapor. As a low‐cost, very simple Se vapor supply method, it can be used as a large‐area Se supply equipment simply by extending the shower area. A significantly higher Ga content was obtained in the space charge region and the highest open‐circuit voltage of 638 V among the CIGS absorbers obtained by 2‐step selenization process.